Jan Van Eyck Academie Maastricht NL : Jaarboek 2005 : Onderzoeksprojecten, Curricula vitae, Jaarprogramma, Institutionele informatie. - Brams, Koen; Guicherit, Armand; Jeught, Petra Van der; Schumacher, Laurens; Tattersall, Dorrie (Maastricht : Jan Van Eyck Akademie Maastricht, 2006)
Andrade Tudela, Armando ; Andreasen, Kasper ; Aracagök, Zafer ; Balier, Ralph ; Barry, Orla ; Benzaquen, Stéphanie ; Van den Brande, Kristien ; Buth, Peggy ; Choi, Min ; Choi, Sulki ; Cuyvers, Wim ; Van Dessel, Marthe ; Gansterer, Nikolaus ; Garrison, Geoffrey ; Hagenbeek, Natascha ; Harris, Yolande ; Hendrikse, Paul ; Infanger, Sarah ; Issa, Lina ; Kakhidze, Alevtina ; Kirsch, Johanna ; Kleerebezem, Jouke ; Konrad, Aglaia ; Kruk, Vinca ; Kwan, Will ; Lapitkova, Zuzana ; Macari, Lucia ; Markusen, Lene ; Mellegers, Adriaan ; Meyer, Eva ; Moth, Charlotte ; Murphy, John ; Pisano, Falke ; Sachs, Hinrich ; Seibold, Stefanie ; Stojnic, Ingrid ; Tacq, Filiep ; Traoré, Saliou ; Uroda, Toni ; Valdes, Francisco ; van der Velden, Daniël ; de Vet, Annelys ; Zimprich, Inga
Nederlands
boek